1983
DOI: 10.1073/pnas.80.13.3963
|View full text |Cite
|
Sign up to set email alerts
|

Buffer gradient gels and 35S label as an aid to rapid DNA sequence determination.

Abstract: Two methods for increasing the length of DNA sequence data that can be read off a polyacrylamide gel are described. We have developed a rapid way to pour a buffer concentration gradient gel that, by altering the vertical band separation on an autoradiograph, allows more sequence to be obtained from a gel. We also show that the use of deoxyadenosine 5'-(a-[3S]thio)triphosphate as the label incorporated in dideoxynucleotide sequence reactions increases the sharpness of the bands on an autoradiograph and so incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
662
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,104 publications
(662 citation statements)
references
References 10 publications
0
662
0
Order By: Relevance
“…This vector is identical to pSK(-) except that it contains a HincII-EcoRV deletion in the polylinker, making it useful for the gene disruptions described below. Single-stranded DNA templates were prepared from the resulting clones and used for DNA sequence analysis as described previously (Sanger et al, 1977;Biggin et al, 1983). The 5'-terminal non-coding sequences of CKI2 were determined from the 2.5-kb genomic clone by the dideoxy chain termination method applied to denatured doubleMolecular Biology of the Cellstranded DNA (Sambrook et al, 1990).…”
Section: Dna Sequencingmentioning
confidence: 99%
“…This vector is identical to pSK(-) except that it contains a HincII-EcoRV deletion in the polylinker, making it useful for the gene disruptions described below. Single-stranded DNA templates were prepared from the resulting clones and used for DNA sequence analysis as described previously (Sanger et al, 1977;Biggin et al, 1983). The 5'-terminal non-coding sequences of CKI2 were determined from the 2.5-kb genomic clone by the dideoxy chain termination method applied to denatured doubleMolecular Biology of the Cellstranded DNA (Sambrook et al, 1990).…”
Section: Dna Sequencingmentioning
confidence: 99%
“…This and similar analysis of subcloned fragments revealed that most of the insert in CP1 was required for complementation. The entire -7.0-kb insert in CP1 was sequenced by using the dideoxynucleotide chain termination method (Sanger et al, 1977) modified for the use of 35S-dATP (Biggin et al, 1983) and T7 polymerase (Sequenase; USB, Cleveland, OH). A series of unidirectionally deleted templates for sequencing was generated by transferring restriction fragments isolated from the insert in CP1 into the vector pVZ1 and employing the exonuclease III method (Henikoff, 1987).…”
Section: Cloning and Sequencing Of The Esp1 Locusmentioning
confidence: 99%
“…We determined the nucleotide sequences of the cDNAs encoding Xenopus LDH-A, LDH-B, and LDH-C, pig LDH-A and LDH-B, and rat LDH-B and LDH-C. 11 We have used these seven LDH sequences deduced from their cDNA sequences and 22 other published LDH sequences, plus three unpublished fish LDH-A sequences, to analyze the evolutionary relationships ofLDH isozymes from mammals, birds, an amphibian, fish, barley, and bacteria.…”
mentioning
confidence: 99%